2003
DOI: 10.1002/app.12022
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation of silk fibroin by sulfuric acid and anticoagulant activity

Abstract: Silk fibroin (Bombyx mori) was sulfated with an aqueous sulfuric acid solution. The sulfated fibroin was characterized by Fourier transform infrared spectroscopy (FTIR), amino acid analysis, and gel filtration chromatography (GFC). Maximum yield was obtained at around 2-4 h, and it decreased at 6 h and more. The molecular size decreased and dispersed with sulfation, and the molecular weight was estimated at around 10,000 by GFC using protein standards. The amino acid composition indicated that the crystal regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Optimization of the homogeneous sulfation condition: Generally, the anticoagulant activity of the sulfated polymer strongly depends on the amount of the incorporated sulfate group [9,10]. Therefore, to investigate the optimal condition, the amount of sulfur bound to SF was adopted to follow the sulfation extent as a function of the reaction temperature and time, and the amount was determined by elemental analysis and expressed as the weight ratio of sulfur to carbon (S/C) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of the homogeneous sulfation condition: Generally, the anticoagulant activity of the sulfated polymer strongly depends on the amount of the incorporated sulfate group [9,10]. Therefore, to investigate the optimal condition, the amount of sulfur bound to SF was adopted to follow the sulfation extent as a function of the reaction temperature and time, and the amount was determined by elemental analysis and expressed as the weight ratio of sulfur to carbon (S/C) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The sulfation of polymers is an approach to model the structure of heparin, a highly sulfated polysaccharide and a commonly used anticoagulant. Heparinlike modification has proved to be an effective way to improve the anticoagulant activity of the polymers [3,[9][10][11]. The sulfation was investigated also for purpose of comparing with the previous heterogeneous sulfation which had disadvantage of severe SF hydrolysis [10].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it can be found that in the area of position [6][7][8][9][10][11][12] th , it has a significant conservative of amino acid Hydropathy. Base on Panek's scale [15], G is a separate class, R, K, E, H are strongly hydrophilic, S, T are weak hydrophilicity.…”
Section: The Statistical Analysis Of Sequence Segmentmentioning
confidence: 99%
“…In 2003, Tamada has researched sulfation of protein, and modified sulfated silk fibroin by concentrated sulfuric acid. They got silk fibroin sulfated efficiency, and found that the reaction efficiency is not high and is very susceptible to decomposition of the sample [9]. Monigatti et al have done a statistical analysis on Tyrosine which may be sulfated in 5 proteins, and given the analysis regularity of Tyrosine sulfation in 2002 [4].…”
Section: Introductionmentioning
confidence: 99%
“…There were only a couple of reports by Tamada et al, in which they demonstrated the method of sulfation of B. mori SF and subsequently proved its anticoagulant activity. [20][21] They have proposed that sulfation results in the addition of sulfate groups to hydroxyl moieties of Ser and Tyr residues in SF. However, in the above reports they have not i) used SF in 3D scaffold form, ii) studied its potential for TE applications, or, iii) performed detailed characterization of the biological properties of SF before and after sulfation.…”
mentioning
confidence: 99%